Improvement of Selected Soil Physical Properties and Mustard Yield After the Application of Tithonia Compost in Ultisols - Apriliani, Ririn; Sulistyo, Bambang; Muktamar, Zainal (BPFP Universitas Bengkulu, 2024)
Ultisols are widespread in the Indonesian archipelago and have potential for developing the agricultural sector. However, Ultisols have several problems, such as low organic matter content, poor soil structure, unstable soil aggregates, high soil bulk density, and low total soil pore space. These problems result in slow soil infiltration and permeability, which can interfere with plant growth. This study aimed to determine the best dose of tithonia compost to improve certain soil physical properties and increase the yield of green mustard in Ultisols. The study was conducted from March to May 2024 at the Greenhouse of the Department of Crop Production, Faculty of Agriculture, University of Bengkulu. This study used a Completely Randomized Design (CRD) with 6 treatments of tithonia compost doses with 3 replications. The treatments were 0 (control), 5, 10, 15, 20, and 25 ton ha-1. After mustard harvesting, undisturbed soil sample was collected from each polybag and analyzed for soil moisture, bulk density, and soil permeability. Fresh and dry weight of mustard were also measured after harvesting. The results showed that the highest improvement of selected soil physical properties was soil fertilized with tithonia compost at the rate of 15 ton ha-1, as shown in the decrease of bulk density and increase in soil moisture content, total pore space, and soil permeability. The application of tithonia compost at 5 ton ha-1 was adequate for the improvement of selected soil physical properties and nutrient release to the soil for green mustard cultivation. The findings of the study will benefit to crop management, especially mustard yield using tithonia compost in Ultisols.